2020
DOI: 10.1016/j.sapharm.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The community pharmacy setting for diabetes prevention: A mixed methods study in people with ‘pre-diabetes’

Abstract: Conflicts of interest CLK and TK are employees of Boots UK. CLK is part of the PhD research team and TK is employed part-time as a pharmacist whilst undertaking her PhD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 46 publications
0
26
0
1
Order By: Relevance
“…The subsample participants were selected by random Semi-structured interviews, inductive thematic analysis (Braun and Clarke) Not described Setting: The study was part of a larger project where people with prediabetes participated in a 3‐week community‐based lifestyle intervention in Western Canada, “Small Steps for Big Changes Program (SSB)”. Participants were interviewed prior to involvement in the intervention Area for lifestyle change (intervention): To promote exercise and dietary changes Bean et al, 2020, Canada [ 49 ] Two-fold purpose of the study: a) Profiling patterns of women’s perceived PA journey over one year in those who engaged in Small Steps for Big Changes (SSBC) and b) understanding strategies used to engage in and maintain PA Participants were a) between 18- and 65-years old b) able to read and speak English, c) identify as a woman, d) have prediabetes (glycated haemoglobin 5.7% to 6.4%), and e) have completed SSBC n = 14* F = 14 Age range: 48–63 Mean age: 60.07 *A subsample of participants from a larger study on diabetes prevention who were female and eligible for SSBC participation, were invited to participate in the qualitative sub study Qualitative semi-structured interviews, face-to-face and telephone interviews Trajectory approach coupled with a deductive-inductive thematic analysis (Braun and Clarke) Not described Setting: The study is a follow-up to a three-week community-based diabetes prevention program in Canada; Small Steps for Big Changes (SSBC) Participants were interviewed at baseline, during and after the intervention Area for lifestyle change (intervention): To promote exercise and dietary changes Katangwe et al, 2020, England [ 50 ] Exploring factors influencing engagement with the National Health Service (NHS) DPP and the role of community pharmacies (CP) in diabetes prevention Eligible patients for referral: individuals 18 years or over with HbA1c blood test results within the pre-diabetes range (42–47 mmol/mol [6.0–6.4%]) in the last 12 months n = 16* F = 9 M = 7 Mean age: 68.4 *A subsample of participants from a larger study on diabetes prevention were purposively sampled from the questionnaire respondents for follow-up semi-structured interviews ( n = 10) and a focus group ( n = 6) Explanatory sequential mixed method design Focus groups and semi-structured interviews (telephone) Thematic analysis (Braun and Clarke) COM- B approach, theoretical model for identifying key factors influencing desired behaviours Setting: Individuals were invited to participate in the NHS DPP in order to lower their risk of developing T2D. In the interview study sample, three had attended the program, three had completed the program, three were waiting, two had dropped out, and five had...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subsample participants were selected by random Semi-structured interviews, inductive thematic analysis (Braun and Clarke) Not described Setting: The study was part of a larger project where people with prediabetes participated in a 3‐week community‐based lifestyle intervention in Western Canada, “Small Steps for Big Changes Program (SSB)”. Participants were interviewed prior to involvement in the intervention Area for lifestyle change (intervention): To promote exercise and dietary changes Bean et al, 2020, Canada [ 49 ] Two-fold purpose of the study: a) Profiling patterns of women’s perceived PA journey over one year in those who engaged in Small Steps for Big Changes (SSBC) and b) understanding strategies used to engage in and maintain PA Participants were a) between 18- and 65-years old b) able to read and speak English, c) identify as a woman, d) have prediabetes (glycated haemoglobin 5.7% to 6.4%), and e) have completed SSBC n = 14* F = 14 Age range: 48–63 Mean age: 60.07 *A subsample of participants from a larger study on diabetes prevention who were female and eligible for SSBC participation, were invited to participate in the qualitative sub study Qualitative semi-structured interviews, face-to-face and telephone interviews Trajectory approach coupled with a deductive-inductive thematic analysis (Braun and Clarke) Not described Setting: The study is a follow-up to a three-week community-based diabetes prevention program in Canada; Small Steps for Big Changes (SSBC) Participants were interviewed at baseline, during and after the intervention Area for lifestyle change (intervention): To promote exercise and dietary changes Katangwe et al, 2020, England [ 50 ] Exploring factors influencing engagement with the National Health Service (NHS) DPP and the role of community pharmacies (CP) in diabetes prevention Eligible patients for referral: individuals 18 years or over with HbA1c blood test results within the pre-diabetes range (42–47 mmol/mol [6.0–6.4%]) in the last 12 months n = 16* F = 9 M = 7 Mean age: 68.4 *A subsample of participants from a larger study on diabetes prevention were purposively sampled from the questionnaire respondents for follow-up semi-structured interviews ( n = 10) and a focus group ( n = 6) Explanatory sequential mixed method design Focus groups and semi-structured interviews (telephone) Thematic analysis (Braun and Clarke) COM- B approach, theoretical model for identifying key factors influencing desired behaviours Setting: Individuals were invited to participate in the NHS DPP in order to lower their risk of developing T2D. In the interview study sample, three had attended the program, three had completed the program, three were waiting, two had dropped out, and five had...…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported on the participant perceived facilitators and barriers of lifestyle change when taking part in community-based lifestyle intervention programs [ 34 , 36 40 , 46 51 , 53 ], while seven studies reported on the participants perceived facilitators and barriers of lifestyle change through consultations with health care providers (no intervention involved) [ 35 , 41 45 , 52 ]. Thirteen studies [ 35 37 , 39 , 41 , 45 50 , 52 , 53 ] reported on the barriers and facilitators of lifestyle change and behavioural change maintenance, addressing both exercise and diet (participants exposed to an lifestyle intervention in nine studies, whereas no intervention in four studies), four studies [ 38 , 40 , 42 , 43 ] reported on exercise only (participants exposed to an lifestyle intervention in two studies, whereas no intervention in two), and three studies [ 34 , 44 , 51 ] reported on diet only (participants exposed to an lifestyle intervention in two studies, whereas no intervention in one).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Community pharmacies have been critical partners for the CDC given that they facilitate access to many preventive services and are perceived by individuals with prediabetes as an acceptable setting for receiving the NDPP. 9 In fact, the CDC launched a multi-year effort in 2017 to engage with pharmacy stakeholders, including professional pharmacy organizations, to create the "Rx for the National Diabetes Prevention Program: Action Guide for Community Pharmacists (Pharmacy Action Guide)", released in May…”
Section: Introductionmentioning
confidence: 99%
“…Community pharmacies have been critical partners for the CDC given that they facilitate access to many preventive services and are perceived by individuals with prediabetes as an acceptable setting for receiving the NDPP. 9 In fact, the CDC launched a multi-year effort in 2017 to engage with pharmacy stakeholders, including professional pharmacy organizations, to create the “Rx for the National Diabetes Prevention Program: Action Guide for Community Pharmacists (Pharmacy Action Guide)”, released in May 2018. 10 The Pharmacy Action Guide provides three levels of pharmacy involvement, including: 1) Promoting awareness of prediabetes and the NDPP, 2) screening individuals for prediabetes and referring them to a NDPP in their area, or 3) delivering the NDPP themselves ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%